Anestesi Spinal pada Seksio Sesaria Wanita dengan Karsinoma Nasofaring - Supraptomo; Uyun, Yusmein (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Introduction. Regional anesthesia and general anesthesia can be performed in patients with nasopharyngeal cancer, although spinal anesthesia is more aggressive lowering the patient’s hemodynamic state, but the likelihood of difficult intubation in these patients becomes a consideration for regional anesthesia. Case. 35-year-old woman, G3P1A1, 37 weeks pregnant in hospital wanted to give birth. Pasr medical history was difficult to swallow with pain and diagnosed with nasopharyngeal carcinoma. Spinal anesthesias was performed with lidocaine 5% dose 75 mg with adjuvant fentanyl 25 ug. Block achieved until dermatome thorakal. The duration of surgery is 60 minutes with systolic between 90-120 mmHg, diastolic between 55-80 mmHg and pulse between 100-112 times / min. Baby born with APGAR score 8-9, weight 3300 gram. Post surgery patients are treated at the Intensive Care Unit, and during treatment the hemodynamic condition is stable. Summary. The technique of spinal block anesthesia with lidocaine 5% 75 mg with adjuvant fentanyl 25 mcg was considered quite satisfactory as anesthesia management in this case. Synergistic effects of local anesthesia and opiod provide great benefits for obtaining adequate anesthesia, thereby reducing the risk of difficult intubation if general anesthesia is performed